Use of Propranolol in Infantile Hemangioma Resulting in Scarless Healing - Rachel Vania; Denny Irwansyah (Majalah Kedokteran Bandung, 2019)
Infantile hemangiomas (IHs) are the most common childhood tumors. Some can ulcerate causing pain, bleeding, and scarring, leading to cosmetical disfigurement. The use of propranolol has beaten the traditional high-dose systemic corticosteroids therapy, which falls short on its infamous adverse effects. In these case series, regimen of propranolol was highlighted when surgery is not an option. Two cases were presented. Case 1 involveda three-month-old baby girl was presented with a 0.6x0.6 cm disfiguring purple tumor on her nasal tip and columella and Case 2 involveda three-month-old baby girl with a 2x0.5 cm sharply bordered and bulging red tumor on her left labium major.Both lesions became visible at the age of 3 months and grew rapidly since then.  Propranolol was initiated at 2 mg/kgBW per day with careful administration. Adverse effects and drug tolerance were closely monitored under pediatrician and plastic surgery care with none reported. Dramatic results was seen after 2 weeks of treatment and no scar was found at the end of the therapy. This confirmed that propranolol is an effective and well tolerated treatment when commenced early and continued with the minimum protocol of 2 mg/kgBW/day through the proliferative phase of infantile hemangioma. It is concluded that propranolol is beneficial for managing infantile hemagioma cases with a scarless outcome that cannot be achieved through surgery. The use of propanolol is extremely beneficial when the case involves a tumor in a site that makes it impossible for reconstruction. Penggunaan Propranolol pada Hemangioma Infantil yang Menghasilkan Penyembuhan Tanpa Bekas LukaHemangioma infantil adalah tumor yang paling sering pada anak. Tumor ini dapat mengalami ulserasi, nyeri, perdarahan, parut buruk, sampai menyebabkan penampilan cacat. Terapi propranolol telah mengalahkan kortikosteroid, yang dikenal mempunyai banyak efek samping yang buruk. Pada serial kasus ini, kami akan menyoroti regimen penggunaan propranolol, ketika pembedahan tidak mungkin dilakukan. Kasus 1: Bayi perempuan, 3 bulan, datang dengan tumor keunguan yang menyebabkan disfigurasi pada nasal tip dan kolumela. Kasus 2: Bayi perempuan, 3 bulan, datang dengan tumor kemerahan, berbatas tegas dan benjol, pada labium mayor sinistra. Kedua lesi timbul pada usia 3 bulan dan membesar dalam hitungan hari. Propranolol dimulai dengan dosis 2 mg/kg/BB per hari, dengan pengawasan ketat oleh spesialis anak dan bedah plastik. Kedua kasus tidak terdapat efek samping dan toleransi obat baik. Hasil drastis terlihat dalam dua minggu dan pada akhir terapi didapatkan parut yang kasat mata. Kasus kami mengonfirmasi bahwa terapi propranolol adalah efektif dan dapat ditoleransi dengan baik, diberikan dini dan stabil pada dosis 2 mg/kg/BB per hari pada fase proliferasi, dengan hasil tanpa bekas yang tidak dapat dicapai dengan pembedahan. Kami ingin meningkatkan kesadaran pada dokter dalam penggunaan propranolol yang telah dibuktikan bermanfaat, terutama pada tumor yang berada di tempat yang tidak dapat dioperasi dan sulit direkonstruksi.